2018
DOI: 10.1515/eces-2018-0020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on the Production of Volatile Fatty Acids in Dark Fermentation Process of Organic Waste

Abstract: The aim of this study was to investigate the effect of pH on the dark fermentation process of kitchen waste by specifying the composition of the volatile fatty acids (VFA), H2 and by drawing the carbon balance. Studies were carried out in 8 dm 3 batch bioreactor in mesophilic conditions. The kitchen waste from the city of Lodz were used as a substrate. Based on the study, it was observed that most of the VFA was produced during the first two days of the process, while in the following days the production was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
6
2
Order By: Relevance
“…The lowest valeric content was observed at pH 12. This is opposite to the findings of Grzelak et al 23 . who reported maximum VFA content under alkaline conditions of pH 10–12.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The lowest valeric content was observed at pH 12. This is opposite to the findings of Grzelak et al 23 . who reported maximum VFA content under alkaline conditions of pH 10–12.…”
Section: Resultscontrasting
confidence: 99%
“…The lowest valeric content was observed at pH 12. This is opposite to the findings of Grzelak et al 23 who reported maximum VFA content under alkaline conditions of pH 10-12. No butyric or propionic acid was detected in any of the pH treatments, except at pH 4.…”
Section: Effect Of Ph On Vfa Production and Compositioncontrasting
confidence: 99%
“…The bioreactor pH was maintained at 7.0 ± 0.1 in all experimental runs. This pH value has been selected based on our own research [33] and available topical literature [27,34] confirming the highest VFAs yields in neutral pH. An increased production of VFAs in each of the processes was observed at the initial days of transient state.…”
Section: An Impact Of Olr and Hrt On Vfas Synthesismentioning
confidence: 99%
“…The butyric acid metabolic pathway is activated to counteract pH drop and, therefore, it is favoured at pH below 6 [68]; whereas the metabolic pathway of Equation ( 1) allows for biogas richer in H 2 . If the metabolic shift is delayed or avoided, it is obvious that the % H 2 in the biogas remains high.…”
Section: Dark Fermentation Kinetics and Parametersmentioning
confidence: 99%